Agricultural processing enterprises: Development potentials and links to the smallholder - Abbott, John C. (International Food Policy Research Institute, 1994)
In countries where farming and fishing are major productive activities, processing enterprises can have a strategic developmental role. Infrastructural, institutional, and contractural issues arise around them. Whereas consumption and nutrition effects of agricultural commercialiazation linked to specific processing enterprises are traced in some of the detailed studies in Part V (for example, export vegetables, chapter 12; spices plantation, chapter 14; dairy, chapter 15; sugarcane factories, chapter 13 and 16), this chapter gives an overview of the broader experiences, potentials and problems of agricultural processing enterprises.